1,3-Dipolar Cycloaddition of 5,6-Dihydroimidazo[2,1-b]thiazolium Betaines - Kim, D.J.; Yoo, K.H.; Park, S.W. (1992)
5,6-Dihydroimidazo[2,1-b]thiazolium betaines were generated in situ from 3,7-disubstituted 5,6-dihydroimidazo[2,1-b]thiazolium bromides and triethylamine. The reaction of these imidazothiazolium betaines with acetylenic dipolarophiles, such as ethyl propiclate, dimethyl acetylenedicarboxylate, and dibenzoylacetylene, provided geometric cis,trans isomers containing 2,3-dihydro-1H-pyrrolo[1,2-a]imidazole. We have proposed a mechanism of this reaction that involves 1,3-dipolar cycloaddition, isomeric rearrangement, and then nucleophilic addition successively. The ratio of trans and cis isomers depended on the temperature and solvents. The stereoselectivity of trans isomers increased with increasing temperature and decreasing polarity of solvents. ？ 1992, American Chemical Society. All rights reserved.